Revision of the genus Andraegoidus Aurivillius (Insecta: Coleoptera: Cerambycidae) - R., Juan Pablo Botero; Monné, Marcela L. (Zootaxa, 2012)
A revision of the genus Andraegoidus Aurivillius, 1920, based on a study of external morphology and terminalia, is pre-sented. The genus and species are redescribed; two subspecies are elevated to species level: Andraegoidus fabricii (Du-pont, 1838) status nov. and A. richteri (Bruch, 1908) status nov.; synonyms are proposed: Trachyderes fulvipennis(Dupont, 1838) = A. fabricii and T. zonatus (Dalman, 1823) = A. rufipes (Fabricius, 1787). The genus is composed of 10species and no subspecies: A. cruentatus (Dupont, 1838), A. distinguendus Hüdepohl, 1985, A. homoplatus (Dupont,1838), A. fabricii (Dupont, 1838), A. lacordairei (Dupont, 1838), A. laticollis Tippmann, 1953, A. richteri (Bruch, 1902),A. rufipes (Fabricius, 1878), A. translucidus Botero & Monné, 2011 and A. variegatus (Perty, 1832). A key to species for each gender as well as photographs and geographical distribution maps are provided.